Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

What is the appropriate way to simplify such an expression. i am unsure of how to use the series i know to apply to this situation

$$\sum_{L=0}^{M}s^{L}L^{2}$$

do i modify such a series as power series, or is there a more efficient series to use here?

thank you very much!!

share|improve this question
    
If $M$ were $\infty$, then there is a power-series-based method to simplify the sum. Would it help to have that explained? Or do you need $M$ to be finite? –  alex.jordan Jun 19 '12 at 18:36
    
M is a number that isnt infiniti. thank you for reply, but how to solve for M not infiniti? –  nanme Jun 19 '12 at 18:37
    
out of being curious suppose $\sum_{L=0}^{M}s^{L}L$ would the same method follow –  nanme Jun 19 '12 at 18:54
    
The method I've used in my answer can apply to a sum where the terms are $s^LL^k$, where $k$ is an integer. Even if $k$ is negative, then you just have to make the inside look like an integral rather than a derivative. (However, executing the integral at the end will be harder than executing the derivative.) So yes, this method works with $k=1$ too. –  alex.jordan Jun 19 '12 at 18:58
    
@ alex.jordan : An algebraic explanation to your method is one basis chang on $\mathbb R[X]$. We try express the canonical basis $(1,X,X^2,...)$ with the basis : $(1,X,X(X-1),X(X-1)(X-2), ...à$ and this expression gives a simple way to calculate generalized expression ... –  Mohamed Jun 19 '12 at 19:04
show 1 more comment

3 Answers

up vote 3 down vote accepted

Try to make the inner expression look like a derivative: $$ \begin{align} \sum_{L=0}^M\left(Ls^{L-1}\right)sL & =s\sum_{L=0}^M\left(\partial_ss^L\right)L\\ & =s\partial_s\sum_{L=0}^Ms^LL\\ & =s\partial_s\sum_{L=0}^M\left(Ls^{L-1}\right)s\\ & =s\partial_s\left(s\sum_{L=0}^M\left(Ls^{L-1}\right)\right)\\ & =s\partial_s\left(s\sum_{L=0}^M\partial_ss^L\right)\\ & =s\partial_s\left(s\partial_s\sum_{L=0}^Ms^L\right)\\ & =s\partial_s\left(s\partial_s\frac{s^{M+1}-1}{s-1}\right)\\ \end{align}$$ Now just take it from here, simplifying from the inside out.

share|improve this answer
add comment

Write : $L^2=L(L-1)+L$ and use derivative. For $ L \geq 2$ : $$L^2 s^L = s^2L(L-1)s^{L-2}+ s Ls^{L-1}= s^2(s^L)'' + s (s^L)'$$ We get : $$\sum_{L=0}^M L^2s^L=0^2+1^2 s + s^2 \left(\sum_{L=2}^{M} s^L \right)''+s \left(\sum_{L=2}^{M} s^L \right)'$$

share|improve this answer
    
$L$ is the index in your sum, so I think you must means something else for the first two terms of your left-hand side. –  alex.jordan Jun 19 '12 at 20:00
    
Oops I meant right-hand side :) –  alex.jordan Jun 19 '12 at 20:22
    
@ alex.jordan Thank you very much.I mean :$0^2 s^0 + 1^2 s^1$ –  Mohamed Jul 13 '12 at 1:30
add comment

Rewrite $L^2 = L(L-1)+L. $ Then,

$$\begin{align} \sum_{L=0}^{M} { L^2 s^L } &= \sum_{L=0}^{M} {L(L-1)s^L} + \sum_{L=0}^{M} {Ls^L}\\ &=s^2 \cdot \frac{\partial^2}{\partial s^2} \sum_{L=0}^{M}{s^L} + s \cdot \frac{\partial}{\partial s}\sum_{L=0}^{M} {s^L}\\ \end{align}$$

You can find formulas for the summations with detailed descriptions of their derivations by searching for "Geometric Progression."

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.